Evaluation of the Inhibitory Efficacy of Eugenol against the Pathogen of Fusarium Wilt in Ginger Seedlings - Xian Zhou; Hui-Hui Ma; Shi-Jie Xiong; Ling-Ling Zhang; Xue-Dong Zhu; Yong-Xing Zhu; Li-Rong Zhou (Horticulturae, 2023)
Fusarium wilt, mainly caused by Fusarium oxysporum, affects ginger yield and quality worldwide. To explore a safe and sustainable method of preventing and controlling Fusarium wilt, the inhibitory effects of eugenol on F. oxysporum FOX-1 were analysed in this study. The results showed that eugenol inhibited the reproductive and vegetative growth of F. oxysporum FOX-1 in vitro. Microscopic observations revealed that eugenol disrupted the hyphal morphology of F. oxysporum. In addition, eugenol destroyed the cell membrane integrity of the pathogenic fungi, resulting in the leakage of F. oxysporum FOX-1 intercellular contents, including electrolytes, soluble proteins, nucleic acids, and malonydialdehyde. Results of an in vivo inoculation test showed that eugenol exerted a strong inhibitory effect on Fusarium wilt in ginger seedlings. In summary, eugenol had an inhibitory effect on the growth of F. oxysporum FOX-1 and controlled Fusarium wilt in ginger seedlings. These findings provide a foundation for future development of botanical antifungal agents to manage Fusarium wilt.